A spectrum of clinical severity of recessive titinopathies in prenatal - Qi, Yiming; Ji, Xueqi; Ding, Hongke; Wang, Yunan; Liu, Xin; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2023)
Variants in TTN are associated with a broad range of clinical phenotypes, from dominant adult-onset dilated cardiomyopathy to recessive infantile-onset myopathy. However, few foetal cases have been reported for multiple reasons. Next-generation sequencing has facilitated the prenatal identification of a growing number of suspected titinopathy variants. We investigated 6 affected foetuses from 3 families, completed the intrauterine course of the serial phenotypic spectrum of TTN, and discussed the genotype-phenotype correlations from a broader perspective. The recognizable prenatal feature onset at the 2nd trimester was started with reduced movement, then contracture 3 to 6 weeks later, followed with/without hydrops, finally at late pregnancy was accompanied with polyhydramnio(major) or oligohydramnios. Two cases with typical arthrogryposis-hydrops sequences identified a meta-only transcript variant c.36203-1G>T. Deleterious transcriptional consequences of the substitution were verified by minigene splicing analysis. Case 3 identified a homozygous splicing variant in the constitutively expressed Z-disc. It presented a milder phenotype than expected, which was presumably saved by the isoform of corons. A summary of the foetal-onset titinopathy cases implied that variants in TTN present with a series of signs and a spectrum of clinical severity, which followed the dosage/positional effect; the meta-only transcript allele involvement may be a prerequisite for the development of fatal hydrops.